2009
DOI: 10.2135/cropsci2008.12.0694
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Drought Tolerance in Dry Bean Derived from the Mesoamerican Gene Pool in Western Nebraska

Abstract: Dry bean (Phaseolus vulgaris L.) is highly susceptible to drought stress, and drought affects 60% of global bean production. We evaluated elite exotic dry bean germplasm derived from the Mesoamerican gene pool for drought tolerance, yield, and adaptation to western Nebraska during 2006 and 2007 at three research sites. Seven tropical lines were evaluated with two great northern cultivars (Matterhorn and Beryl‐R) and one pinto cultivar (Bill‐Z) serving as checks. Adjacent nonstressed (NS) and drought‐stressed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 22 publications
4
49
1
2
Order By: Relevance
“…However, contrary to what was expected, some genotypes performed better under moderate drought-stressed conditions than in non-stressed conditions. Similar findings were reported by Urrea et al 31 with the dry bean (Phaseolus vulgaris L.) cultivar SER 22 which performed well under drought-stressed conditions, but below average under non-stressed conditions. These genotypes are classified in the class C according to Fernandez To determine the most suitable drought tolerant criteria, the correlation between Y p , Y s and other drought tolerance indices was computed.…”
Section: Discussionsupporting
confidence: 89%
“…However, contrary to what was expected, some genotypes performed better under moderate drought-stressed conditions than in non-stressed conditions. Similar findings were reported by Urrea et al 31 with the dry bean (Phaseolus vulgaris L.) cultivar SER 22 which performed well under drought-stressed conditions, but below average under non-stressed conditions. These genotypes are classified in the class C according to Fernandez To determine the most suitable drought tolerant criteria, the correlation between Y p , Y s and other drought tolerance indices was computed.…”
Section: Discussionsupporting
confidence: 89%
“…DKF was warmer and had more evapotranspiration than MARC suggesting that the drought stress in DKF was greater than MARC. Urrea et al (2009) has reported that drought stress caused yield reduction ranging from 47 to 69 % compared to the non-stress conditions. Similarly, Rao et al (2013) reported that GY under rainfed conditions reduced by 31 % compared with irrigated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is principally produced in Latin America and eastern and southern Africa where seasonal rainfall is erratic and soil moisture deficit often limits its yield production (Beebe 2012;Urrea et al 2009;Wortmann 1998). Sixty percent of the bean crop is produced under drought stress (Beebe 2012;Rao 2001;White and Singh 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations